The birds of Tefé, Central Amazonia: a historical review, compilation of data, and new records - Guimarães, David Pedroza; de Lima, Ana Caroline Gomes; Pedroza, Diego (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2022)
The municipality of Tefé is located in Central Amazonia, Brazil, where scientists have observed and collected many different types of animals, including birds, since the 19th century. We compiled the records of the bird species collected in ​​the municipality of Tefé from the 19th century to the present day, using data from scientific collections, peer-reviewed and gray literature, and citizen science reports from online platforms. We confirmed records of a total of 342 species from 62 families. The data indicate that the Tefé region is an important route for numerous migratory species, many of which may also breed locally. We also found records of prominent endemic species, such as Psophia leucoptera Spix, 1825 and taxa that are vulnerable to extinction, including Agamia agami (Gmelin, 1789). The presence of floodplain forest specialists especially highlights the value of these environments in the municipality and reinforces the need to establish protected areas. We would also recommend the implementation of urban planning measures to impede the loss of forest areas in the vicinity of the town of Tefé, especially areas in which birdwatching is practiced, given the occurrence of many important species, which can even be observed within the urban zone.
Keywords: Amazonas state; Middle Solimões River; Inambari center of endemism; Floodplain forest; Birdwatching